САМОМЕНЕДЖМЕНТ ЯК ЗАСІБ ПРОФЕСІЙНОГО РОЗВИТКУ ОСОБИСТОСТІ МАЙБУТНІХ ВЧИТЕЛІВ (Педагогіка вищої та середньої школи, 2022)
In this article is spoken about necessity of formation of  students skills to self-management fo r their professional development in the pedagogical sphere.